Bioarchaeology and dietary reconstruction across late antiquity and the Middle Ages in Tuscany, Central Italy - Riccomi, Giulia (Archaeopress archaeology., 2021)
This volume presents the first multidisciplinary bioarchaeological analysis to reconstruct life conditions in ancient Tuscany between Late Antiquity and the Middle Ages. This was done through the examination of stress markers, including adult stature, periosteal reaction, cranial porosities, linear enamel hypoplasia and paleodietary reconstruction.